Adherence to antiplatelet therapy after percutaneous coronary intervention: a population study in a region of Italy. Issue 3 (March 2015) - Pinnarelli, Luigi; Mayer, Flavia; Bauleo, Lisa; Agabiti, Nera; Kirchmayer, Ursula; Belleudi, Valeria; Di Martino, Mirko; Autore, Camillo; Ricci, Roberto; Violini, Roberto; Fusco, Danilo; Davoli, Marina; et al.
Abstract : Aims: We evaluated adherence to dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) for patients in the Lazio region of Italy and the impact of discharge ward type on therapy discontinuation. Methods: From the Hospital Information System, we selected patients who underwent PCI from 2006 to 2007 and obtained Regional Drug Dispense Registry data for antiplatelet drugs prescribed for 12 months after discharge. Appropriate therapy was defined as DAPT with prescribed daily doses for each drug covering at least 75% of each individual follow-up period. The association between discharge ward type and antiplatelet therapy adherence at 12 months post discharge was estimated using multilevel logistic regression analysis. Results: A total of 11 186 patients with PCI were included, and fewer than half (4984; 44.56%) were on adequate DAPT. Only 2930 of 5390 patients (54.36%) with DAPT in the first 6 months post discharge continued DAPT in the second 6 months. Patients discharged from cardiology units or intensive coronary care units were more likely (odds ratio = 1.26; P  = 0.003) to receive appropriate antiplatelet therapy, and elderly patients were less likely (odds ratio = 0.65; P  < 0.001) to do so. Conclusion: The proportion of PCI patients receiving appropriate DAPT after discharge is suboptimal in this region, and elderly patients are less likely to receive appropriate therapy. These findings could be important for improving patient management and ensuring adherence to clinical guidelines and indicate the need for a systematic evaluation of the appropriateness of postdischarge therapy. Abstract : Supplemental Digital Content is available in the text